BHRINGARAJA BHAVITHA GANDHAKA KALPA IN THE MANAGEMENT OF VYANGA - A CASE STUDY - Aparna, Sen; Lakshmi, Thara (International Journal of Ayurveda and Pharma Research, 2019)
Acquired disorders of hyperpigmentation affects individuals of all skin types. In Ayurveda, Vyanga is a Kshudra roga and a Rakta pradoshaja vikara which mainly affects the complexion of a person by producing Niruja, Shyava varna mandalas over face. The aim of the study was to assess the effect of Bhringaraja bhavitha gandhaka kalpa in Vyanga which is the eighth Gandhaka kalpa mentioned in the eight Taranga of Rasatarangini. Variables like percentage of area involved, darkness and homogeneity were assessed before and after treatment. This paper highlights a case study of Vyanga treated with Bhringaraja bhavitha gandhaka kalpa.